Bank Health, Profit Management and Its Impact on National Banking Stock Returns - Sudrajat, Enjat; Masitoh, Masitoh; Marwah, Tia Hidayatul (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The purpose of this study is to provide strong evidence regarding the influence of bank health level measured by NPL, ROA and CAR on Earningt management which has an impact on stock returns. This type of research is included in quantitative research. The population in this study is all Indonesia's national private banking companies listed on the Indonesia Stock Exchange in 2023. Meanwhile, the sample in this study is 37 companies. The type of data used is secondary data obtained from www.idx.co.id. The data collection technique uses documentation techniques. The analysis used in this study is cross section data regression analysis. The results of this study are (1) Non-Performing Loans do not have a significant effect on Earning management. (2) Return On Assets does not have a significant effect on Earning management. (3) Capital Adequacy Ratio does not have a significant effect on Earning management. (4) Earning management has no significant effect on stock returns. (5) Non-Performing Loans do not have a significant effect on stock returns. (6) Return On Assets does not have a significant effect on stock returns. (7) Capital Adequacy Ratio has a significant effect on stock returns. (8) Earning management does not mediate Non-Performing Loans against stock returns. (9) Earning management does not mediate Return On Assets on stock returns. (10) Earning management does not mediate the capital adequacy ratio to stock returns.